Avaliação da qualidade da água para irrigação dos três açudes urbanos do município de Angicos-RN - Costa Silva, Pedro Carlos (Universidade Federal Rural do Semi-Árido, 2019)
The municipality of Angicos is located in the semi-arid region of northeastern Brazil, where climatic conditions cause water shortages that favor high concentrations of substances. Thus, this study aims to evaluate the water quality for irrigation of the three urban dams of the city of Angicos-RN in a gradient of urban occupation, according to CONAMA 357/05. The physicalchemical parameters analyzed, evaluated the soil and plant quality, some of them being Conductivity (EC), chloride (Cl -), sodium (Na +), calcium and magnesium (Ca 2+) and (Mg 2+); as well as the concentration of heavy metals such as copper (Cu), cadmium (Cd) and lead (Pb). Chloride concentrations were found within the parameters established by the standard in the Caraubinhas and Novo Angicos dams, while the José Teodoro reservoir obtained higher concentrations, with results in the range of 10.60 to 11.00 mmolc / L. In the copper analysis, all reservoirs had concentrations higher than allowed (0.009 mg / L). Lead was the heavy metal that registered concentrations only for the José Teodoro reservoir being higher than that established by the legislation (0.01 mg / L). Thus, each of the reservoirs was classified with a quality level for use in the irrigation, being the Caraubinhas reservoir presenting good conditions, the Novo Angicos reservoir with average quality and the José Teodoro reservoir classified as irregular.
Artigo Acadêmico
Keywords: Chumbo; Metais pesados; Reservatório de água; Semiárido; Lead; Heavy metals; Water tank; Semiarid; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA